International Trade and Labor Markets: Evidence from the Arab Republic of Egypt - Raymond Robertson; Mexico Alberto Vergara Bahena; Deeksha Kokas; Gladys Lopez-Acevedo (Institute of Labor Economics (IZA), 2021)
Since the early 1990s, some developing countries have experienced a coincidence of rising exports – especially those related to global value chains – and improved labor market outcomes. During 2000–10, rising trade was associated with falling poverty and inequality in many developing countries. However, the Arab Republic of Egypt was not one of these countries, although it signed several trade agreements. The lack of trade-related improvements in labor market outcomes – including poverty, inequality, average wage levels, informality, and female labor force participation – could be explained by at least two possibilities. First, it is possible that trade agreements did not produce the same increase in trade for Egypt as for other countries. Second, it is possible that exports do not generate the same kinds of changes in labor market outcomes as experienced in other countries. After presenting the trends in key labor market outcomes over 2000–19, this paper evaluates both hypotheses. Using a gravity model approach, the results suggest that the changes in Egypt's exports following trade agreements are above internationally estimated averages. Second, the results from a Bartik approach find no significant relationship between rising exports and wages, informality, or female labor force participation. Additional analysis shows that Egypt's average wage levels are among the highest among countries that export the same goods exported by Egypt, possibly suggesting that Egypt has a relatively weak comparative advantage in currently exported goods, and thus might need to rethink its export basket.
Keywords: J31; F16; 330; labor market outcomes; trade agreements; Egypt